Exploring the conceptualisation and study of freebirthing as a historical and social phenomenon: a meta-narrative review of diverse research traditions. Issue 4 (2nd May 2020) - McKenzie, Gemma; Robert, Glenn; Montgomery, Elsa
Abstract : Freebirthing is a clandestine practice whereby women intentionally give birth without healthcare professionals (HCPs) present in countries where there are medical facilities available to assist them. Women who make this decision are frequently subjected to stigma and condemnation, yet research on the phenomenon suggests that women's motivations are often complex. The aim of this review was to explore how freebirth has been conceptualised over time in the English-language academic and grey literature. The meta-narrative methodology employed enables a phenomenon to be understood within and between differing research traditions, as well as against its social and historical context. Our research uncovered nine research traditions (nursing, autobiographical text with birthing philosophy, midwifery, activism, medicine, sociology, law and ethics, pregnancy and birth advice, and anthropology) originating from eight countries and spanning the years 1957–2018. Most of the texts were written by women, with the majority being non-empirical. Empirical studies on freebirth were usually qualitative, although there were a small number of quantitative medical and midwifery studies; these texts often focused on women's motivations and highlighted a range of reasons as to why a woman would decide to give birth without HCPs present. Motivations frequently related to women's previous negative maternity experiences and the type of maternity care available, for example medicalised and hospital-based. The use of the meta-narrative methodology allowed the origins of freebirth in 1950s America to be traced to present-day empirical studies of the phenomenon. This highlighted how the subject and the publication of literature relating to freebirth are embedded within their social and historical contexts. From its very inception, freebirth aligns with the medicalisation of childbirth, the position of women in society, the provision of maternity care and the way in which women experience maternity services.